The relationship between cardiometabolic Index and diabetic kidney disease in people with diabetes - Kong, Jianping; Tao, Wenting; Sun, Yuhong; Xu, Yong; Li, Hailun; Li, Jing (Frontiers in Endocrinology, 2025)
IntroductionStudies have shown a strong correlation between the cardiometabolic index (CMI) and health issues such as diabetes, atherosclerosis, and decreased renal function. Nevertheless, the correlation between CMI and diabetic kidney disease (DKD) remains ambiguous. The objective of this study is to evaluate the correlation between CMI and DKD in patients with diabetes in the United States.MethodsThe study involved individuals who were part of the National Health and Nutrition Examination Survey (NHANES) conducted between 2003 and 2018. A multivariable logistic regression analysis was employed for investigating the correlation between CMI and DKD. The study employed Generalized Additive Models (GAM) and smooth curve fitting methods for investigating the nonlinear relationship between CMI and DKD. Two-stage regression analysis was applied for investigating threshold effects in the connection between CMI and DKD. In addition, subgroup analysis and interaction tests were also carried out.ResultsThis analysis included a total of 6,540 adults with diabetes. After adjusting for variables including age, sex, race, education level, smoking status, household income and poverty rate, body mass index, hypertension status, aspartate aminotransferase, alanine aminotransferase, serum albumin, and serum globulin, we discovered a significant connection between CMI levels and the risk of DKD (OR=1.11, 95% CI: 1.05, 1.17, p<0.0001). Individuals with varying smoking statuses showed variations in this connection according to subgroup analysis and interaction tests (p for interaction=0.0216). Conversely, this correlation appeared similar across different genders, ages, races, BMI categories, hypertension statuses, and insulin usage among people with diabetes (all p for interaction >0.05). A nonlinear relationship existed between CMI and DKD, with threshold analysis indicating a turning point at CMI=1.7. A positive correlation was observed between CMI levels in people with diabetes and the risk of DKD when CMI exceeded 1.7.ConclusionThe risk of DKD was significantly positively correlated with the CMI levels of people with diabetes. Further larger prospective studies are required to confirm our results.